Kinetics and pathways of ibuprofen degradation by the UV/chlorine advanced oxidation process. (1st March 2016) - Xiang, Yingying; Fang, Jingyun; Shang, Chii
Abstract: The UV/chlorine advanced oxidation process (AOP), which forms reactive species such as hydroxyl radicals (HO ) and reactive chlorine species (RCS) such as chlorine atoms (Cl ) and Cl2 −, is being considered as an alternative to the UV/H2 O2 AOP for the degradation of emerging contaminants. This study investigated the kinetics and pathways of the degradation of a recalcitrant pharmaceutical and personal care product (PPCP)—ibuprofen (IBP)—by the UV/chlorine AOP. The degradation of IBP followed the pseudo first-order kinetics. The first-order rate constant was 3.3 times higher in the UV/chlorine AOP than in the UV/H2 O2 AOP for a given chemical molar dosage at pH 6. The first-order rate constant decreased from 3.1 × 10 −3  s −1 to 5.5 × 10 −4  s −1 with increasing pH from 6 to 9. Both HO and RCS contributed to the degradation, and the contribution of RCS increased from 22% to 30% with increasing pH from 6 to 9. The degradation was initiated by HO -induced hydroxylation and Cl -induced chlorine substitution, and sustained through decarboxylation, demethylation, chlorination and ring cleavage to form more stable products. Significant amounts of chlorinated intermediates/byproducts were formed from the UV/chlorine AOP, and four chlorinated products were newly identified. The yield of total organic chlorine (TOCl) was 31.6 μM after 90% degradation of 50 μM IBP under the experimental conditions. The known disinfection by-products (DBPs) comprised 17.4% of the TOCl. The effects of water matrix in filtered drinking water on the degradation were not significant, demonstrating the practicality of the UV/chlorine AOP for the control of some refractory PPCPs. However, the toxicity of the chlorinated products should be further assessed. Graphical abstract: Highlights: The kinetics and pathways of IBP degradation by the UV/chlorine AOP were investigated. The degradation was rapid and initiated by both HO hydroxylation and Cl substitution. The HO hydroxylation produced intermediates reactive to chlorine species. Significant amounts of chlorinated byproducts were formed in the AOP.